The effect of solute cloud formation on the second order pyramidal to basal transition of 〈c+a〉 edge dislocations in Mg-Y solid solutions. (June 2020) - Utt, Daniel; Stukowski, Alexander; Ghazisaeidi, Maryam
Graphical abstract: Abstract: We study the effect of solute segregation on pyramidal to basal transformation of 〈 c + a 〉 edge dislocations in a model Mg-Y alloy, using a hybrid Monte Carlo/Molecular Dynamics method. While a random solute distribution has no appreciable effect on this undesirable transition, a solute cloud around the dislocation slows and effectively prevents it in case of Mg-3 at % Y alloy. Comparing with the time scale required for diffusion of Y to the dislocation, suggests that segregation of Y and other fast diffusing elements can be engineered to prohibit this glissile to sessile transition, and stabilize the pyramidal glide of 〈 c + a 〉 dislocations.